2018
DOI: 10.1002/jctb.5511
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated poly(arylene ether nitrile)/polypyrrole core/shell nanofibrous mat: an efficient absorbent for the removal of hexavalent chromium from aqueous solution

Abstract: BACKGROUND Sulfonated poly(arylene ether nitrile)/polypyrrole core/shell nanofibrous mats were prepared by an electrospinning technique, followed by in situ polymerization of pyrrole monomer. Their removal of hexavalent chromium (Cr (VI)) from aqueous solution was systematically investigated. The structure and composition of core/shell PEN/PPy nanofibrous mats were examined and confirmed by attenuated total reflectance Fourier transform infrared spectroscopy (ATR‐FTIR), X‐ray photoelectron spectroscopy (XPS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Finally, the adsorption reaches equilibrium in 2 h. Owing to the steric hindrance between solution phase and MB molecules adhering to the absorbent surface, the remaining adsorption sites are hard to occupy. Furthermore, the MB adsorption kinetics of our adsorbent is investigated by pseudo‐first‐order and pseudo‐second‐order models, as shown by the following two equations: lnqnormaleqt=lnqnormalek1t t/qt=1/k2qe2+t/qnormale …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the adsorption reaches equilibrium in 2 h. Owing to the steric hindrance between solution phase and MB molecules adhering to the absorbent surface, the remaining adsorption sites are hard to occupy. Furthermore, the MB adsorption kinetics of our adsorbent is investigated by pseudo‐first‐order and pseudo‐second‐order models, as shown by the following two equations: lnqnormaleqt=lnqnormalek1t t/qt=1/k2qe2+t/qnormale …”
Section: Resultsmentioning
confidence: 99%
“…Typically, the randomness, spontaneity, exothermicity and endothermicity of the adsorption process for as‐prepared adsorbents can be determined by various thermodynamic parameters, including standard entropy change (Δ S °), standard Gibbs free energy change (Δ G °) and standard enthalpy change (Δ H °). In this work, these three thermodynamic parameters are calculated by the following two equations: ΔG°=RTlnKnormalc lnKnormalc=ΔH°/italicRT+ΔS°/R where R , T and K c ( q e / C e ) represent the gas constant, absolute temperature and equilibrium constant respectively. Through the above two equations, a plot of ln K c vs 1000/ T is obtained ( C 0 = 60 mg L −1 ), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The equilibrium adsorption capacities of SPEN-CTAB-0%, SPEN-CTAB-5% and SPEN-CTAB-15% were 183.6, 161.4 and 127.4 mg/g, respectively. In order to better understand the adsorption behavior, the adsorption data were analyzed on the basis of two commonly used kinetic models, namely the first-order kinetic model and second-order kinetic model shown in Equations (5) and (6), respectively [23,26]: logfalse(qeqtfalse)=logqek12.303t tqt=1k2qe2+tqe where t (min) is the adsorption time, k 1 (min −1 ) is the rate constant of pseudo-first-order and k 2 (g/mg min) is the rate constant of pseudo-second-order.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption process is a single layer adsorption, that is, adsorption only occurred on the surface of the adsorbent. The Freundlich model can be applied to both single-layer adsorption and non-uniform surface adsorption, which can describe the mechanism of uneven surface adsorption well [23,26]. According to Figure 7 and Table 5, the obtained R 2 of the Langmuir model (0.9807) was larger than that of the Freundlich model (0.8046), which indicated that the Langmuir model was more applicable to analyze the adsorption isotherm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation